Perancangan Sistem Pengetahuan untuk Meningkatkan Aksesibilitas Informasi Unit Kegiatan Mahasiswa - Sari, Mutiara Novita; Adya, Rahel Saffana; Trikiswoyo, Muhammad Iqbal; Sugiarti, Yuni (INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS : Journal of Information Management; Vol 9 No 2 (2024): INFORMATION MANAGEMENT FOR EDUCATORS AND PROFESSIONALS (DESEMBER 2024), 2024)
Easy access to information is essential for students to support their involvement in campus activities. At Universitas Islam Negeri (UIN) Jakarta, Student Activity Units (UKMs) play a crucial role in fostering student potential. However, limitations in disseminating information about UKM activities hinder student participation. This research aims to design a centralized Knowledge Management System (KMS) prototype to improve the accessibility of UKM activity information and enhance knowledge management. The Rapid Application Development (RAD) method was employed for system development, emphasizing rapid iterations and active user involvement. System modeling utilized Unified Modeling Language (UML), incorporating Use Case Diagrams to represent key functional requirements and Class Diagrams to define data structures and relationships between system components. The KMS prototype includes information search features, documentation, and a discussion forum that supports collaboration among UKM members and makes it easier for general students to access information related to UKM activities. The findings demonstrate that the KMS improves information accessibility, facilitates centralized documentation of UKM activities, and fosters synergy among campus organizations. With this system, students can efficiently find relevant information, leading to increased participation in UKM activities. This prototype provides an effective initial solution to address information access challenges within the UKM environment. It also serves as a foundation for future system enhancements through prototype testing and evaluation.